The impact of preoperative ultrasound and intraoperative findings on surgical outcomes in patients at high risk of placenta accreta spectrum. (7th September 2022) - Hussein, Ahmed M.; Fox, Karin; Bhide, Amar; Elbarmelgy, Rasha A.; Elbarmelgy, Rana M.; Thabet, Mohamed M.; Jauniaux, Eric
Abstract: Objective: To assess whether preoperative ultrasound imaging and intraoperative features predict surgical outcomes in patients at high risk for placenta accreta spectrum (PAS). Design: Cohort study. Setting: Cairo University Maternity, Egypt. Population or sample: Pregnant patients with one or more prior caesarean deliveries presenting with a low‐lying/placenta praevia with or without PAS confirmed by histopathology. Methods: Logistic regression and multivariable analyses. Main outcomes measures: Need for primary caesarean hysterectomy, numbers of red blood cell (RBC) units transfused and patients requiring transfusion of >5 units. Results: Ninety consecutive records were reviewed, including 58 (64.4%) PAS cases. Sixty (66.7%, 95% confidence interval (CI) 56–76) required hysterectomy. Odds of hysterectomy were significantly ( p  = 0.005) increased with complete praevia. Significantly higher odds of hysterectomy were associated with subplacental hypervascularity (7.23, 95% CI 2.72–19.2, p  < 0.001), lacunar scores 2+ and 3+ (12.6, 95% CI 4.15–38.5, p  < 0.001), lacunar feeder vessels (5.69, 95% CI 1.77–18.3, p  = 0.004) or bridging vessels (2.00, 95% CI 1.29–3.10, p  = 0.002) on ultrasound, and increased lower segment vascularization at laparotomy (5.42, 95% CI 2.09–14.1, p  = 0.001). Transfusion >5 RBC units was associated with number of lacunae (odds ratio [OR] 1.48, 95% CI 1.14–1.93, p  = 0.004) and presence of feeder vessels (OR 1.62, 95% CI 1.24–2.11, p  = 0.001). The multivariable analysis indicated that parity, placental location and PAS were significantly ( p  = 0.007; p  = 0.01; p  < 0.001, respectively) associated with hysterectomy. Conclusions: Preoperative ultrasound imaging can assist in triaging and counselling patients regarding the odds of PAS, intraoperative blood losses and need for hysterectomy, and intraoperative features can assist the surgeon in evaluating the need for multidisciplinary support.